KONTRIBUSI KEMAMPUAN APRESIASI SASTRA DAN BERPIKIR KREATIF TERHADAP KETERAMPILAN BERMAIN DRAMA PADA SISWA KELAS XII IPS SMA NEGERI 2 RENGAT KABUPATEN INDRAGIRI HULU - Wilda Srihastuty Handayani Piliang; Atmazaki .; Syahrul R (Fakultas Bahasa dan Seni UNP, 2014)
Abstract: This research is motivated by observations and interviews that have been doing research. The interview results indicate that dramatic play skills are still short of the standards expected. This phenomenon is thought to have something to do with the ability of appreciation of literature and creative thinking of students. Based journals and theory experts also stated that there is a contribution of literary appreciation ability and creative thinking skills to play the drama. Based on these problems, this study aimed to clarify whether or not the contribution of literary appreciation and the ability to think creatively, either separately or jointly to the drama students playing skills. Related to the problems and research objectives, methods used in this study is the correlation method. This correlation method aims to reveal the relationship between the variables under study. The study population was all students of class XII IPS SMAN 2 Rengat Indragiri Hulu in the academic year 2013/2014, amounting to 115 students and the study sample was 50 students by using probability sampling techniques. This research instrument in the form of objective tests, creativity tests verbal, and test performance. Data analysis was performed using the PPM correlation, multiple correlation test, t test, F test and regression test. To determine the contribution between the variables under study, used the formula coefficient of determination. The results showed that (1) there is a contribution to the literary appreciation ability to play drama skills in a positive and significant; (2) there is a contribution to the ability of creative thinking skills play a positive and significant drama; (3) the contribution of literary appreciation and the ability to think creatively together to role-play skills in a positive and significant. Therefore, the higher the ability of appreciation of literature and creative thinking of students, the higher the drama playing skills. Kata kunci: kemampuan apresiasi sastra, kemampuan berpikir kreatif, keterampilan bermain drama